Effect of islamic and conventional bonds on firm's performance: evidence from Malaysia - Nur-Al-Ahad, Md.; Jamadar, Yasmin; Abdul Latiff, Ahmed Razman; Tabash, Mosab I. (IEEE, 2022)
This study aims to examine the impact of Islamic and Conventional bonds on firm performance. Using Malaysian listed companies from 2010 to 2018, the results of the multiple regression analyses show that the bond affects firm performance measured by Return on Assets (ROA) and Return on Equity (ROE). Moreover, we also examine whether the bond affects the firm value (measured by EPS) or not. Results provide mixed results for both conventional and Islamic bonds. The results show that the issuance of conventional bonds positively affects the firm's performance. However, the findings also reveal that the Islamic bond-to-debt ratio negatively affects firm ROA. Next, Islamic bond has a negative effect on ROE. Further, results also reveal that the total debt ratio positively relates to firm performance. On the other hand, both conventional bonds and Islamic bonds have a negative association with the firm value. This study shows that either type of bond is good for companies up to a certain threshold. The manager should deliberate the sensitivity of Islamic bonds while investing.